Effect of heating rate on oxidation process of fine-dispersed ZnS:Mn obtained by SHS - Bacherikov, Yu.Yu.; Zhuk, A.G.; Okhrimenko, O.B.; Kardashov, D.L.; Kozitskiy, S.V.; Kidalov, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The influence of annealing at 350 °C in air atmosphere on the luminescent characteristics of powdered ZnS: Mn obtained by self-propagating high-temperature synthesis has been studied. It was shown that variation in material heating rate due to changes in the annealing temperature results in different behavior of oxidative processes. It has been ascertained that the slow heating of powdered ZnS:Mn, compared with the rapid one in the presence of oxygen, promotes active oxidation of ZnS and formation of Frenkel pairs, increases mileage of defects acting as sensitizers, and their localization near Mn²⁺. The model which explains the observed changes in the luminescence and PLE spectra has been presented.